PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA OUTLET NYENYES PALEMBANG - Nofiawaty .; Beli Yuliandi (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The research is conducted to identify how much influence the general interior, store layout, and interior display affect the decision to buy by consumers of Nyenyes Palembang Outlet. The Data are analyzed by the application of multiple linear regression test, that is, t test and f test. SPSS version 12.00 for Windows is used to compute the test. The respondents consist of 52 customers of the outlet. The F test and t test show that the store atmosphere variable, that is, general interior (X1), Store layout (X2), and Interior design (X3) indicate a significant influence on the decision to buy by Nyenyes Palembang Outlet consumers. The linear regression computation result in Y=(a)3.039 + 0.225(X1) + 0.046( X2) + 0.077X3 indicating that the most dominant factor is genera interior.